Strong opioid consumption and its correlation with pain intensity and inpatient complexity. A 6‐year analysis in a tertiary hospital. (4th April 2020) - Monge‐Escartín, Inés; Montes, Antonio; Comas, Merce; Grau, Santiago
Abstract: Background: An increasing trend in opioid consumption has been observed worldwide in last decades. However, data related to opioid utilization in hospital settings are scarce. The aim of this study was to determine the evolution of use of strong opioids and pain intensity in a tertiary hospital during 6 years. Methods: Consumption of strong opioid analgesics used at the hospital at any time between 2012 and 2017 was collected. Data were expressed on oral morphine equivalents (OMEs) per 100 bed‐days. Pain intensity was measured by the numerical rating scale (NRS) and the percentage of patients who experienced a NRS value ≥3 and ≥7 were calculated. Case mix index (CMI) was also collected. Data were quantified in medical and surgical area separately. Results: Consumption of opioids varied from 812.4 to 1, 038.8 OMEs/100 bed‐days and from 967.3 to 1, 023.7 in medical and surgical area. The percentage of patients that experienced a value of NRS ≥ 3 and ≥7 in medical area increased from 24.2% and 5.5% to 31.7% and 7.5%, ( p = .038, p = .040). It was observed a correlation between the percentage of patients that experienced a NRS ≥ 7 in two consecutive determinations and opioid prescription in medical area ( p = .039).The CMI increased from 1.05 and 0.91 to 1.18 and 1.04 in medical and surgical area ( p = .020, p = .004). Conclusions: Consumption of strong opioids has remained stable, both in medical and surgical area, during last years. A correlation between prescription of opioids and pain intensity is observed in case of repeated and severe pain in medical departments. Significance: This study shows a stable consumption of strong opioid analgesics in a hospital setting in contrast to what appears to be the extrahospitalary trend during last years. The association between consumption of opioids and pain intensity seems to indicate a good control of pain in the clinical setting, showing a significant correlation between the consumption of opioids and repeated and severe pain in medical departments.